1999
DOI: 10.1007/s004150050367
|View full text |Cite
|
Sign up to set email alerts
|

l -2-Hydroxyglutaric aciduria: two Japanese adult cases in one family

Abstract: We report two adult Japanese sisters with L-2-hydroxy-glutaric aciduria (acidemia), both of whom were much older (aged 57, 47 years old) than previously reported patients (from neonate to 44 years old), and who presented with differing severity. Magnetic resonance imaging revealed typical subcortical white matter lesions in both cases and showed brainstem atrophy and thickness of the calvarium in the elder sister. L-2-Hydroxyglutaric acid levels were increased in urine, plasma, and cerebrospinal fluid. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…Because the exact time of onset in these two patients is unknown, they were not included in the mean age of onset. The cases in the literature reported as adult onset [Fujitake et al, 1999;Goffette et al, 2006] were diagnosed during adulthood but, in retrospect, the patients also had symptoms during childhood. In fact, the disease has an insidious onset and it is therefore not possible to pinpoint a specific time of onset.…”
Section: Clinical Phenotypementioning
confidence: 99%
“…Because the exact time of onset in these two patients is unknown, they were not included in the mean age of onset. The cases in the literature reported as adult onset [Fujitake et al, 1999;Goffette et al, 2006] were diagnosed during adulthood but, in retrospect, the patients also had symptoms during childhood. In fact, the disease has an insidious onset and it is therefore not possible to pinpoint a specific time of onset.…”
Section: Clinical Phenotypementioning
confidence: 99%
“…L2HGA with mild phenotype has been previously described [2,14]. However, acute unprovoked decompensation as may occur in other aminoacidopathies, and occurred in this case, has not been previously described in L2HGA.…”
Section: Sirsmentioning
confidence: 44%
“…There are less than 20 adult reports of L2HGA (average age at time of diagnosis 30; age range at time of diagnosis 18-57), with all patients having a history of developmental delay in childhood [1][2][3][4][5][6][7][8]. L2HGA typically presents in the first year of life with non-specific motor delay and later cognitive and motor developmental delay in childhood [1,9].…”
Section: Sirsmentioning
confidence: 99%
“…The information currently available on mutations underlying L-2-HGA provides no evidence for a correlation of individual mutations with the spectrum or severity of clinical symptoms. Notably, in clinical reports on siblings with L-2-OH-GA, including one case with proven homozygosity for the same mutation (Rzem et al 2004), pronounced differences in the clinical presentation have been observed (Fujitake et al 1999;Goffette et al 2006). A better understanding of interacting factors in the pathway of L2HGDH will be necessary for a better understanding of the influences on the phenotype.…”
Section: Discussionmentioning
confidence: 92%